Self-esteem level and development of communication skills in emblematic schools of Ayacucho - Rodriguez Cuadros, Sadid Natali (2023)
In this study, the research goal was to know the relationship between the selected variables, which were the level of self-esteem, including dimensions that are involved, and the development of communication skills in the Emblematic Educational Institutions in the Ayacucho region in the year 2022, in order to achieve the objectives set forth in this research, which was descriptive, with a correlational design, a questionnaire was used as a collection instrument to measure the level of self-esteem of the students, and the documentary review to extract information regarding the development of communication skills. The sample was constituted by 130 students from different Emblematic Educational Institutions of the Ayacucho region. The information collected was treated with the support of Spearman's Rho statistician, achieving from the statistical verification (p=0.000<0.05; Rho = 0.498), concluding that there is a direct and significant relationship between the level of self-esteem and the development of competencies. communication in students of the emblematic Educational Institutions of the Ayacucho region.